2019
DOI: 10.1016/j.jsat.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of enhanced telephone monitoring with detoxification patients: 3- and 6-month outcomes

Abstract: Telehealth interventions have the potential to deter repeated detoxification episodes and improve outcomes. Using a sample of 298 detoxification inpatients, this randomized controlled trial compared Enhanced Telephone Monitoring (ETM) to usual care (UC) on the primary outcome of reducing subsequent detoxification, and secondary outcomes of linking patients to addiction treatment and mutual-help, and patients' experience of improved substance use and mental health outcomes. At the 3-month follow-up (i.e., at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…62 In addition to linkage through VTCs, research has shown that substance use patients and patients with cooccurring substance use and mental health disorders can be successfully linked to treatment and to 12-step groups, which in turn improves substance use and mental health as well as criminal justice-related outcomes. [63][64][65] These linkage interventions are brief and practical to apply on a routine basis in health care settings and could be investigated in selected samples of veterans with a history of criminal activity.…”
Section: Building a Research Agendamentioning
confidence: 99%
“…62 In addition to linkage through VTCs, research has shown that substance use patients and patients with cooccurring substance use and mental health disorders can be successfully linked to treatment and to 12-step groups, which in turn improves substance use and mental health as well as criminal justice-related outcomes. [63][64][65] These linkage interventions are brief and practical to apply on a routine basis in health care settings and could be investigated in selected samples of veterans with a history of criminal activity.…”
Section: Building a Research Agendamentioning
confidence: 99%
“…To date, although a cascade of neurotransmitter and neuroendocrine abnormalities and neuronal damage are well-recognized consequences following long-term abuse of illegal substances, only limited molecular biomarkers have been identified for the associated symptoms (Volkow et al, 2015). Diagnosis is thus mainly left to the use of subjective questionnaires, particularly during the detoxification stage within the first 3 to 6 months (Stein et al, 2020;Timko et al, 2019). We observed that the plasma serotonin was significantly increased in patients with SUDs and anxiety (HAM-A) was significantly correlated with higher plasma serotonin concentration as compared with HCs, supporting the notion that changes in plasma serotonin seem to be more associated with the presence of psychiatric comorbidity than other neurotransmitters such as GABA and choline (Araos et al, 2019;Fava et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Third, this study will examine the duration of intervention needed to produce optimal effects. Outside of studies that have tested telephone-based continuing care for patients receiving addictions treatment [[84], [85], [86], [87], [88], [89]], few behavioral alcohol interventions have based the number of sessions and the duration of the intervention on empirical data, relying instead on clinical judgement, precedent, or pilot testing to set these intervention parameters. The present study is novel in its inclusion of intervention quantity/duration as an experimental factor in an alcohol intervention among people with HIV.…”
Section: Discussionmentioning
confidence: 99%